2019
DOI: 10.1093/mnras/stz2866
|View full text |Cite
|
Sign up to set email alerts
|

LOFAR early-time search for coherent radio emission from GRB 180706A

Abstract: The nature of the central engines of gamma-ray bursts (GRBs) and the composition of their relativistic jets are still under debate. If the jets are Poynting flux dominated rather than baryon dominated, a coherent radio flare from magnetic re-connection events might be expected with the prompt gamma-ray emission. There are two competing models for the central engines of GRBs; a black hole or a newly formed milli-second magnetar. If the central engine is a magnetar it is predicted to produce coherent radio emiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 109 publications
(200 reference statements)
0
7
0
Order By: Relevance
“…LOFAR has performed successful triggered observations of GRB 180706A (Rowlinson et al 2019) & GRB 181123B (Rowlinson et al 2021). The former was a long GRB but the latter was a short GRB, and its afterglow has been associated with a galaxy at z=1.8 (Paterson et al 2020) with a chance alignment of 0.44%.…”
Section: Current Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…LOFAR has performed successful triggered observations of GRB 180706A (Rowlinson et al 2019) & GRB 181123B (Rowlinson et al 2021). The former was a long GRB but the latter was a short GRB, and its afterglow has been associated with a galaxy at z=1.8 (Paterson et al 2020) with a chance alignment of 0.44%.…”
Section: Current Generationmentioning
confidence: 99%
“…Making use of direction-dependent calibration and source subtraction techniques, Rowlinson et al (2019) were able to place deep fluence limits, corresponding to 3 × 10 3 Jy ms for a typical sGRB of redshift 𝑧 = 1 7 . Given this, and the results of Tian et al (2022), we find that triggered observations by LOFAR and MWA will detect pre-merger coherent emission to a distance of approximately 3 − 5 𝜂 1/2 −2 𝐵 𝑠,12 Mpc, using detection limits in Table 2.…”
Section: Current Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The prominent role of magnetars as promising candidates for extragalactic FRB sources has fostered a number of complementary attempts to identify counterparts or associations with other classes of known sources: since magnetars are believed to represent the endpoint of some core-collapsed progenitors of long GRBs (e.g., [56][57][58]), as well as the result of a compact binary merger signalled by a short GRB (e.g., [59][60][61]), some of these GRB sources were targeted by radio follow-up observations, either within hours of the GRB or years later, to search for FRB emission [62][63][64][65][66][67]. Systematic and sensitive searches for emission compatible with MGFs from well localised FRB sources have also been carried out in parallel, both independently of and simultaneously with radio observations, whose results and implications are presented in Section 6.…”
Section: Magnetarsmentioning
confidence: 99%
“…To date, there have been many searches for FRB emission below 300 MHz, including simultaneous, multiband, targeted (Law et al 2017;Sokolowski et al 2018;Houben et al 2019) and widefield blind (Coenen et al 2014;Karastergiou et al 2015;Tingay et al 2015;Rowlinson et al 2016;Sanidas et al 2019) searches using LOFAR, the Murchison Wide-field Array (MWA) and the Long-wavelength Array. In addition, searches for prompt and dispersed (FRB-like) signals predicted to be associated with gammaray bursts have also been conducted with MWA and LOFAR via rapid-response observations (Kaplan et al 2015;Rowlinson et al 2019Rowlinson et al , 2021Anderson et al 2021;Tian et al 2022a,b), none of which have yielded a detection. However, recently Pleunis et al (2021a) reported the detection of 18 bursts from FRB 20180916B between 110-188 MHz using LOFAR, the only detections of any FRB below 300 MHz to date.…”
Section: Introductionmentioning
confidence: 99%